PTU-042 Post polypectomy bleeding (PPB) in the english nhs bowel cancer screening programme (NHSBCSP). (22nd June 2015) - Derbyshire, E; Nickerson, C; Hungin, A; Rutter, MD
Abstract : Introduction: Colonoscopies in the English NHSBCSP are offered to 60–74 year olds with an abnormal Faecal Occult Blood Test. Polypectomy breaks the adenoma-carcinoma sequence but carries a risk of adverse events such as Post Polypectomy Bleeding (PPB). The NHSBCSP has a longstanding robust mechanism for capturing and reviewing adverse events. Adverse Events are graded by severity using the NHSBCSP framework, based on the American Society of Gastrointestinal Endoscopy grading system. 1, 2 We aimed to (1) determine the rate of PPB, broken down by severity grading, in one region of the NHSBCSP and (2) describe PPB management and outcomes. Method: This prospectively collected observational case series identified patients with PPB at 5 Bowel Cancer Screening Centres within the North East Region of the English NHSBCSP from the 06/12/2010 to 15/07/2014. Patient co-morbidity, use of anticoagulation, polyp location, morphology, size, polypectomy method, time to presentation, subsequent patient management and outcome were all recorded. PPB was graded as major, intermediate or minor as per the NHSBCSP grading system. Results: From a total population of 4, 191, 507, 15, 285 colonoscopies were subsequently performed on 11, 564 patients leading to 23, 766 polypectomies. 68 colonoscopies with PPB were identified; a PPB rate of 0.44% per colonoscopy and 0.29% per polypectomy. 2.9% of cases were major due to need for surgery or admission to the Intensive Care Unit for > 1 night; median time to presentation was 3.5 days (range 1–6 days), median hospital stay was 3 days (range 2–4 days). 41.2% of cases were intermediate, the majority due to need for repeat endoscopy or in patient admission > 4 nights; median time to presentation was 5 days (range 0–19 days), median hospital stay was 2 days (range 0–6 days). Overall, 8.8% of patients presented with symptoms or signs of haemodynamic compromise. 19.1% of patients required intravascular resuscitation with intravenous fluids and/or Red Blood Cells. Repeat endoscopy was performed in 27.9% with repeat endoscopic therapy in 10.3%. Surgery was performed in 1.47% of cases. 1.47% of patients required a second admission and were managed radiologically. Conclusion: We believe this detailed, robustly collected and prospectively categorised dataset gives a true reflection of PPB rate among experienced colonoscopists. A PPB rate of 0.44% is therefore excellent when compared with other similar series. 2.9% of PPB cases were major, 41.2% were intermediate and 55.9% were minor; therefore clinically significant bleeding occurred in only 44.1% of cases. Disclosure of interest: None Declared. References: Chilton A, Rutter M. NHS BCSP Publ . No 6, 2011 Cotton PB, et al . Gastrointest Endosc. 2010;71:446–54